2022
DOI: 10.1002/dmrr.3514
|View full text |Cite
|
Sign up to set email alerts
|

C‐peptide, glycaemic control, and diabetic complications in type 2 diabetes mellitus: A real‐world study

Abstract: Objective: To explore the relationship between C-peptide and glycaemic control rate and diabetic complications (microvascular complication and cerebral infarction) and provide evidence for stratified treatment of type 2 diabetes mellitus (T2DM)based C-peptide.Method: This is a cross-sectional real-world observational study. According to the inclusion and exclusion criteria, we studied 1377 patients with T2DM, grouped by fasting C-peptide and HOMA-IR. Blood samples were collected after fasting overnight. Logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…The relationship between insulin resistance and kidney disease is complex. A similar real‐world study 22 also from Chinese T2DM patients showed that the relationship between C‐peptide and diabetic kidney disease follows a U‐style curve. Insulin resistance is a common early change in CKD and is almost universal in end‐stage renal disease 25 .…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The relationship between insulin resistance and kidney disease is complex. A similar real‐world study 22 also from Chinese T2DM patients showed that the relationship between C‐peptide and diabetic kidney disease follows a U‐style curve. Insulin resistance is a common early change in CKD and is almost universal in end‐stage renal disease 25 .…”
Section: Discussionmentioning
confidence: 74%
“…21 This study classified patients based on specific FCP levels, a specific phenotypic measure. In addition, Yajing Huang et al 22 neuropathy in patients with T1 and T2DM was significantly higher than that in patients with the other two types of T2DM. Insulin deficiency or hyperglycaemia seems to be an important cause of retinopathy.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The elevated serum level of Lp(a) was associated with renal impairment in T2DM patients independent of albuminuria and insulin resistance [ 29 ]. Excessive C-peptide may promote renal function loss and the incidence of DKD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted October 8, 2022. ; https://doi.org/10.1101/2022.10.07.22280304 doi: medRxiv preprint features of DR and DKD: DR is characterized by vascular permeability and retinal neovascularization, while DKD is featured with glomerular sclerosis. It has been revealed that the associations of several clinical indicators with DR and DKD are different, for example, C peptide 6 , glycated albumin to glycated hemoglobin (HbA1c) ratio 7 , and age 8 .…”
Section: Introductionmentioning
confidence: 99%